Application of the Public-Private Partnership Concept in Airport Development in Bintan Regency to Enhance the Coastal Economy - Rizki Gunawan; Rumzi Samin (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2024)
The efforts of various regions to introduce the identity and beauty of their areas are often hindered by inadequate infrastructure and poor management by local governments. Additionally, funding, which is critical for development, poses a significant challenge. As a solution, Public-Private Partnerships (PPP) offer an alternative approach to budgeting and financing that extends beyond the use of regional (APBD) and national (APBN) budgets. In Bintan Regency, various infrastructure developments aimed at supporting the tourism sector have been undertaken. Notably, PT. Angkasa Pura II, in collaboration with PT. Bintan Aviation Investments, is committed to constructing an international airport designed with Airport Resort Facilities, named Bintan New Airport or Busung Airport, to bolster the economy of Bintan Regency. However, the study reveals that the development, which is anticipated to become a cornerstone of economic strength in Bintan Regency, faces significant challenges from the Airport Business Entity (BUBU). This has resulted in delays and complications in the continuation of the airport construction project between PT. Angkasa Pura II and PT. Bintan Aviation Investments. Despite these obstacles, the partnership remains focused on achieving its goal of enhancing the regional economy through improved infrastructure and tourism facilities. he collaboration between PT. Angkasa Pura II and PT. Bintan Aviation Investments represents a strategic move to leverage private sector efficiency and innovation in public infrastructure projects. Nonetheless, the ongoing challenges with the Airport Business Entity highlight the complexities involved in such partnerships, necessitating careful management and oversight to ensure project continuity and success.